Diabetic nephropathy - Jordanova Elena; Simić-Ogrizović Sanja; Pavlović Tanja (Halo 194, 2018)
Diabetes mellitus is one of the most prevalent chronical non-communicable diseases and is a huge public health problem. Diabetic nephropathy is a microvascular complication of both insulin dependant and insulin independent diabetes mellitus and is characterized by persistent proteinuria, accompanied by hypertension and retinopathy, but without urinary tract infection, other kidney disease or heart failure. According to the newest Annual report on dialysis treatment and transplant surgery in Serbia for the year 2015, hypertension and diabetic nephropathy were the most common causes of terminal renal failure (51.5%); the percentage of new diabetic patients was 22.6%. About 2/3 of all patients diagnosed with manifested diabetic nephropathy die of cardiovascular disease even before their kidney disease progresses to the final stage of renal insufficiency. Risk factors for the development of diabetic nephropathy are: gender, age, genetic factors, hyperglicemia, hypertension, dyslipidemia, hypoprotein nutrition and smoking. Diabetic nephropathy shall not develop if there is no hyperglicemia, regardless of genetic predisposition and all other risk factors. The phases of development of diabetic nephropathy are: glomerular hyperfiltration, latent phase, mycroalbuminuria, macroalbuminuria, chronic kidney disease development. The most important measures of prevention for diabetic nephropathy are: maintenance of glicemia and HbA1C < 7.0% as close as possible to the recommended target level ranges, blood pressure reduction and maintenance at the target range of 130/80, blocking the renin angiotensin aldosterone system, stopping smoking, avoiding nephrotoxic agents - NSAID, aminoglycoside antibiotics, radiocontrast media; treatment of hyperlipidemia, physical activity, weight reduction in overweight patients. The Steno 2 study emphasised the importance of a multifactorial approach to the prevention of proteinuria. It is expected that new drugs, that will affect certain growth factors, AGEs or reactive oxygen radicals, vasoactive factors which include endothelial receptor blockers, shall be efficient in the prevention of diabetic nephropathy.